The Existence of Regional-Owned Liability Companies as Profit-Oriented Regional-Owned Enterprises - Suratminingsih, Endang (Global Legal Review, 2024)
Regional-Owned Enterprise (“BUMD”) is a business entity owned by the regional government as a source of local revenue, especially to provide benefits to the regional economy based on Good Corporate Governance. In addition to seeking profit, Regional Companies also carry out social functions for the residents of their regions. Before the era of regional autonomy, regional companies were regulated by Law No. 5 of 1962 concerning Regional Companies. Responding to this, the government together with the People's Representative Council (“DPR”) replaced the Law on Regional Companies with the Law on Regional Government and Government Regulations on BUMD. The two regulations were drafted to improve the performance of regional companies, as well as to fill the legal vacuum regarding regulations regarding BUMD. In practice, the purpose of establishing the BUMD has not been achieved because BUMD is required to have a social function in society, which makes it less focused on its main mission. Using a normative juridical research method and statutory approach as well as conceptual approach, this paper comprehensively examines Regional Liability Company (“Perseroda”) regulations and offers an ideal concept for the existence of profit-oriented Perseroda in Indonesia. The legal theories used are the Theory of Three Fundamental Legal Values (Gustav Radbruch) and the Legal Entity Theory. The results of the research show that the most appropriate solution is to have the management of BUMD separate from the Regional Government Law and that the issuance of Government Regulations regarding BUMD is proven yet to be able in addressing the problem of BUMD management. Therefore, it is recommended that the DPR and the Government immediately organize and harmonize regulations regarding BUMD management so as to realize good BUMD governance and performance, especially to support the strength of the regional economy.